Molecular Mechanism of the Regulatory Effect of Schisandrol A on the Immune Function of Mice Based on a Transcription Factor Regulatory Network - Xu, Guangyu; Feng, Yanbo; Li, Han; Chen, Cong; Li, He; Wang, Chunmei; Chen, Jianguang; Sun, Jinghui (Frontiers in Pharmacology, 2021)
The aim of this study was to explore the molecular mechanism of the regulation of Schizandrol A (SA) on the immune function of immunosuppressive mice induced by cyclophosphamide. On the basis of the screened 1619 differentially expressed genes related to the regulation of SA on the immune function of mice in our previous study, the transcription factors and their corresponding target genes were screened through Transcriptional Regulatory Element Database (TRED), and the transcription factor target gene regulatory network was constructed. The key nodes of the network were statistically analyzed to clarify the role of transcription factors in the regulatory network. The correlation of network genes with diseases was analyzed with the online annotation tool through Database for Annotation, Visualization and Integrated Discovery (DAVID). Finally, the key factors related to the regulation of SA on the immune function of mice were screened out, and verified by animal experiments and the detection of related protein expressions by Western blot method. The results showed that SA could alleviate the immunosuppression induced by cyclophosphamide in mice and regulate the expression of Jun, Trp53 and Creb1 proteins in the spleen tissue of mice, and the potential mechanism may be that SA, together with transcription factors Atf4 and E2f2, participates in regulating the immune function of mice through Atk1, Trp53, Creb1, Casp3, Pten, Cdkn1A and Jun, and Jun, Trp53 and Creb1 play an important role in it by regulating HIF-1 signaling pathway, indicating that SA can regulate the immune function of mice through multiple genes and their transcription factors to play a role in the alleviation of some immunity-related diseases (such as cancer).